Ability of Beauveria bassiana to suppress Colletotrichum truncatum and increase the growth of chili plants (Capsicum annuum) - Yanty, Dini Puspita; Trizelia, Trizelia; Darnetty, Darnetty; Trisno, Jumsu (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2024)
Anthracnose is a disease caused by Colletotrichum sp., which can reduce the quality and yield of red chili by 45-60%. This study aimed to determine the ability of different Beauveria bassiana isolates to control anthracnose in chili. The research employed a Randomized Block Design (RBD) consisting of 6 treatments and 5 replications. The treatments included a control and 5 different B. bassiana isolates (PD114, TD312, WS, BbKo, KT2B21). The observed variables included incubation period, disease incidence and severity, plant height, number of leaves, flowering time, and chili fruit weight. The results showed that the application of different B. bassiana isolates have effectively inhibited the development of Colletotrichum truncatum, which caused anthracnose in chili. B. bassiana has demonstrated the ability to prolong the incubation period of C. truncatum (5.40 days) and reduce the percentage of disease incidence (16%). Furthermore, the application of B. bassiana increased the height of chili plants (40.40 cm) and the number of leaves (32 leaves), accelerated the flowering time (42.80 days), and boosted chili production (178.25 g). The WS and TD312 isolates revealed the most significant results. Although the severity of the disease was not impacted, the 2 isolates provided notable agronomic benefits to the chili plants.